Iliad - Homer; Butler, Samuel tr. (Singapore Penguin Random House, 2024)
Often considered the first great book of literature, The Illiad is an epic poem which set the stage for all larger-than-life dramas the creative world has since witnessed. It tells the story of the darkest episode of the most retold Trojan War. It$1 (Bs an epic poem, with beautiful lyrical tone, set around an eternal love story, an eternal friendship, and an eternal enmity. At the centre of the story is Achilles, the greatest warrior-champion of the Greeks, the great principled and morally upright King Priam offering valuable insights to life, the beautiful Helen and all the mistakes one makes in love, war, and life. The Illiad is a must read for all fond of beautifully strung words that pull at heart strings with a deep sense of catharsis.s
Keywords: Fiction- English; Novel- English